TUBERCULOSE LATENTE EM PACIENTES VIVENDO COM HIV: ANÁLISE DA CASCATA DO CUIDADO CONTÍNUO - Jannayna Hammoud Brandão (2021)
Introduction: The management of the cascade of care in latent tuberculosis infection (LTBI) is one of the fundamental pillars in the elimination of tuberculosis in the world. Objective: To analyze the cascade of continuous care of latent tuberculosis in people living with HIV in a reference service TB-HIV in Mato Grosso do Sul. Methods: Based on secondary data, we conducted a cross-sectional and analytical study with individual patient information from retrospective pharmacy treatment records, clinical data from medical records, and tuberculin test (TT) records or LTBI investigation from January 2011 to July 2020. Results: We identified six stages of the care cascade; a total of 1,966 HIV patients were enrolled in UNIDIP´s Logistics Drug Control System in 2019, which corresponds to stage one of identification. In step two, testing 9.26% (78/842), had LTBI identification and 10.46% (78/745), after excluding unread tests, considering as a cutoff point ≥ 5mm. 0.89% were LTBI despite negative TT and 0.17% were identified as LTBI without laboratory testing. In nine years, 42.82% (842/1966) had TT and the non-return for reading was 11.52% (97/842). Of the patients who started HIV follow-up in 2019, 46.75% (72/154) were the ones who took most of the TT, in contrast to those who were already retained in the service and who also took the test in the same year 12.03% (218/1812). In step three, all patients with LTBI were excluded for active tuberculosis, using radiology. In step four, of the prescription treatment, from 2018, after the new recommendations, 6.89% (2/29) of the treatments were indicated without laboratory evidence and TCD4 <350 cells/mm3, and 3.44% (1/29) with TCD4 <350 cel/mm3, negative TT and active TB contact, and 89.65% (26/29) tuberculin/e or IGRA tests were used as evidence. In step five, of the patients eligible for treatment, 37.14% (26/70) did not start treatment, since the majority 69.23% (18/26) the test result was not checked or there was a loss of outpatient follow-up. In stage six, 67.44% (29/43) completed treatment, 30.23% (13/43) abandoned and 2.32% (1/43) were suspended due to adverse reactions. Being a drug user was a factor associated with the abandonment of preventive treatment (p=0.016). Conclusion: There are flaws in the cascade of care in LTBI, whose barriers reduce access to the TT, return to the reading of the test, annual testing throughout HIV follow-up, the indication of testing and treatment, and monitoring of preventive treatment. The protocol proposed using immunological status by the Ministry of Health was not implemented, evidencing the importance given by the physician to use laboratory evidence to indicate treatment. Being a drug user was a risk factor associated with the abandonment of preventive treatment. Qualitative studies to identify barriers, beliefs, and values related to preventive treatment are fundamental for the implementation of strategies for the management of the care cascade in LTBI. Keywords: Cascade of continuous care. Latent tuberculosis. Latent tuberculosis infection. People living with HIV.